Towards a use of “legal design thinking” techniques in tax law studies - Antón Antón, Álvaro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
To build a relationship between Tax Administration and taxpayers based on trust, law science must provide the necessary information related to policies or institutions but also inform taxpayers about their rights and obligations. This information must be known but, above all, understood. The objective is to introduce a paradigm shift in the way legal studies are approached through Legal Design thinking techniques. Specifically, starting from the need for the jurist to study the law, collaborating with other disciplines to design mechanisms that allow the communication of complex information that helps both the understanding of the law and decision-making process.